Analysis, Synchronization, and Robotic Application of a Modified Hyperjerk Chaotic System. (30th April 2020) - Moysis, Lazaros; Petavratzis, Eleftherios; Marwan, Muhammad; Volos, Christos; Nistazakis, Hector; Ahmad, Salman
Abstract : In this work, a novel hyperjerk system, with hyperbolic sine function as the only nonlinear term, is proposed, as a modification of a hyperjerk system proposed by Leutcho et al. First, a dynamical analysis on the system is performed and interesting phenomena concerning chaos theory, such as route to chaos, antimonotonicity, crisis, and coexisting attractors, are studied. For this reason, the system's bifurcation diagrams with respect to different parameter values are plotted and its Lyapunov exponents are computed. Afterwards, the synchronization of the system is considered, using active control. The proposed system is then applied, as a chaotic generator, to the problem of chaotic path planning, using a combination of sampling and a modulo tactic technique.